2012
DOI: 10.1007/s00264-012-1543-4
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of intertrochanteric bone quality in osteoporotic female rats after injection of polylactic acid-polyglycolic acid copolymer/collagen type I microspheres combined with bone mesenchymal stem cells

Abstract: Purpose Osteoporosis mainly involves cancellous bone, and the spine and hip, with their relatively high cancellous bone to cortical bone ratio, are severely affected. Studies of bone mesenchymal stem cells (BMSCs) from osteoporotic patients and animal models have revealed that osteoporosis is often associated with reduction of BMSCs' proliferation and osteogenic differentiation. Our aim was to test whether polylactic acidpolyglycolic acid copolymer(PLGA)/collagen type I(CoI) microspheres combined with BMSCs co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…Thirteen (81%) of the 16 studies that reported BV/TV demonstrated a statistically significant increase in BV/TV in groups treated with BMAC compared with untreated control groups. 6,18,19,21,24,27,28,34,36,39,45,48 Two studies showed semi-quantitative improvement in bone volume using micro-CT. 23,29 Thirty-two (91%) of 35 studies evaluated bone regeneration either histologically or histomorphometrically using primarily a hematoxylin-eosin stain or Safranin O stain. 3,6,8,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][34][35][36][37][38][40][41][42][43][44][45]48 Nineteen (90%) of 21 studies that performed statistics reported a statistically significant increase in percentage of new bone formation in the experimental groups containing BMAC versus the control group.…”
Section: Evaluation Of Outcomesmentioning
confidence: 98%
See 2 more Smart Citations
“…Thirteen (81%) of the 16 studies that reported BV/TV demonstrated a statistically significant increase in BV/TV in groups treated with BMAC compared with untreated control groups. 6,18,19,21,24,27,28,34,36,39,45,48 Two studies showed semi-quantitative improvement in bone volume using micro-CT. 23,29 Thirty-two (91%) of 35 studies evaluated bone regeneration either histologically or histomorphometrically using primarily a hematoxylin-eosin stain or Safranin O stain. 3,6,8,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][34][35][36][37][38][40][41][42][43][44][45]48 Nineteen (90%) of 21 studies that performed statistics reported a statistically significant increase in percentage of new bone formation in the experimental groups containing BMAC versus the control group.…”
Section: Evaluation Of Outcomesmentioning
confidence: 98%
“…Twelve (34%) studies used a rat model. 3,8,20,23,[33][34][35][36][37][38][39] Of the rat models, 11 investigated the femur and 1 investigated the radius. Four studies (11%) used a goat model.…”
Section: Evaluation Of Animal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Allogeneic and autologous stem cell transplantation has also been considered for research in osteoporotic bone [9,73]. Yu et al [73] injected collagen I-coated PLGA microspheres enriched with allogeneic bone mesenchymal stem cells (BMSC's) from healthy rats into a drill-hole defect in the greater trochanter of osteoporotic rats.…”
Section: +mentioning
confidence: 99%
“…Yu et al [73] injected collagen I-coated PLGA microspheres enriched with allogeneic bone mesenchymal stem cells (BMSC's) from healthy rats into a drill-hole defect in the greater trochanter of osteoporotic rats. BMD, trabecular thickness, trabecular spacing and bone volume fraction were found to be better than in the control group.…”
Section: +mentioning
confidence: 99%